Artful Pathways to Interreligious Understanding: Student Responses on STE(Arts)M Integration Through Maker Education in Interreligious Learning - Hosic, Rusmir; Abrori, Fadhlan Muchlas; Lavicza, Zsolt; Anđić, Branko; Kreis, Yves (Greek Journal of Religious Education (GjRE), 2024)
Religious diversity in Austria, particularly between Muslims and Catholics, is currently receiving significant attention, especially in primary schools. As a result, we are conducting interreligious learning activities to assist students in comprehending and appreciating the teachings of different religions. To enhance the appeal of interreligious learning, we integrated it with STEAM (Science, Technology, Engineering, Arts, and Mathematics) and maker education. The study contributes to the existing body of research on interreligious learning and maker education, emphasizing the suitability of these approaches in promoting interreligious understanding, critical thinking, artistic expression, and meaningful learning.